Attractors of dynamical systems with control: topology of purposeful formation - Sparavalo, M. K. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
The definitions of homogeneous and mosaic attractors of codimension one are given. A topological method for their purposeful formation by using the feedback control laws of controlled dynamical systems is suggested.